Moral Entertainment - The Buddhist Hell Parks of Thailand - Husarski, Roman (2021)
Visiting Hell parks is a popular pastime in contemporary Thailand. Situated near Buddhist temples, these gruesome sculpture gardens depict the Buddhist vision of Hell. These grotesque and violent sculptures are usually seen as an oddity and a form of low art. Perhaps for this reason, they are rarely studied by scholars. This article focuses on the parks as modern entertainment. Usually found in rural areas, these spots try to answer the challenges of the commercialisation and globalisation of Thai society. A detailed analysis of four Hell parks, Wang Saen Suk, Wat Pa Lak Roi, Wat Pa Non Sawan and Wat Pa Thewapithak, shows that these religious amusement parks serve not only as means of entertainment but are also places of Buddhist morality.
Keywords: Buddhist art; Buddhist hell; Hell parks; Thai Buddhism; morality and religion; moralność i religia; piekielne parki; piekło buddyjskie; political science of religion; politologia religii; sztuka buddyjska; tajski buddyzm